Forms of Faith : Literary form and religious conflict in Early Modern England. - Baldo, Jonathan; Karremann, Isabel (Manchester : Manchester University Press, 2017)
This collection of essays opens a new perspective on the interplay of religious conflict and literary culture in early modern England. Placing the focus on negotiation instead of escalation, thirteen distinguished international scholars explore the specific ways available to mediate, displace or suspend confessional conflict in and through literature.
9 Henry V and the interrogative conscience as a space for the performative negotiation of confessional conflictNotes; 10 Formal experimentation and the question of Donne's ecumenicalism; Notes; 11 Foucault, confession, and Donne; Seeing the divided body of Christ; The fecundity of true religion; Notes; Afterword: Reformed indifferently ; Notes; Index.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 050, 072, 082, 650 - OCLC control number change
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism -- Congresses; Religion and literature -- England -- History -- Congresses; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Electronic books